Frontotemporal Lobar degeneration with TDP-43 presenting as progressive supranuclear palsy syndrome - Aya Murakami; Shunsuke Koga; Hiroaki Sekiya; Masataka Nakamura; Yusuke Yakushiji; Dennis W. Dickson (Acta Neuropathologica Communications)
Abstract Objective Frontotemporal lobar degeneration with TDP-43 pathology (FTLD) usually presents with frontotemporal dementia, semantic aphasia or progressive nonfluent aphasia. Corticobasal syndrome and atypical parkinsonism have been occasionally reported, but progressive supranuclear palsy (PSP) syndrome (also known as Richardson syndrome (RS)) has not been reported in patients with FTLD-TDP. In this study we report clinical and pathologic characteristics of FTLD-TDP, clinically diagnosed as PSP syndrome (FTLD-TDP-PSP). Methods We reviewed clinical information of 270 patients with FTLD-TDP from the Mayo Clinic brain bank and identified 5 patients with FTLD-TDP-PSP. As a control group, we selected ten consecutive patients of pathologically confirmed PSP with clinical presentations of PSP syndrome (PSP-RS). We compared the clinical and pathological features of FTLD-TDP-PSP and PSP-RS. Results The most common clinical symptoms in FTLD-TDP-PSP were memory loss (100%) followed by parkinsonism (80%), early falls (60%), and behavioral variant FTD (60%). All patients with PSP-RS met the Movement Disorder Society’s criteria for probable PSP, while only one FTLD-TDP-PSP met the probable PSP. Two of the five patients with FTLD-TDP-PSP had moderate or severe neuronal loss in the substantia nigra and one had moderate or severe neuronal loss in the putamen and globus pallidus. Conclusion A small subset of patients with FTLD-TDP can, in rare instances, present with symptoms associated with PSP. Therefore, FTLD-TDP may be considered in differential diagnosis, especially in patients who do not meet the diagnostic criteria. Our findings emphasize the need for further clinical and biomarker studies of FTLD-TDP.